2017
DOI: 10.1159/000467393
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Advanced Bone Age in Childhood Obesity

Abstract: Background: Childhood obesity is associated with advanced bone age (BA). Previous studies suggest that androgens, oestrogens, sex hormone-binding globulin, and insulin are responsible for this phenomenon, but results are contradictory and might be biased by confounders. We aim to elucidate this matter by applying a multivariate approach. Method: We performed a correlation analysis of BA standard deviation score (SDS) with age- and sex-specific SDS for androgens, oestrogens, and with indicators of insulin secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 30 publications
6
25
1
Order By: Relevance
“…Similar to the ndings by Kwon et al [23] and others [20,24], our study showed a positive association between serum DHEAS SDS and advanced BA. This relationship is likely due to the higher adrenal androgen levels in children with obesity; these increased levels are believed to be responsible for the advanced BA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to the ndings by Kwon et al [23] and others [20,24], our study showed a positive association between serum DHEAS SDS and advanced BA. This relationship is likely due to the higher adrenal androgen levels in children with obesity; these increased levels are believed to be responsible for the advanced BA.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, in a study of 66 prepubertal children with obesity and premature adrenarche, an exploratory stepwise regression model showed that weight, oestradiol and DHEAS were the strongest predictors of BA/CA, accounting for 24% of the variance [20]. Another study in 101 obese children generated a backward regression analysis model in which sex, DHEAS SDS, and age explained 27% of the total variance in BA SDS [24]. Therefore, there may be other underlying causes of advanced BA, including genetic causes such as heterozygous mutations in ACAN [28] and extrinsic factors such as exposure to endocrine-disrupting chemicals [29].…”
Section: Discussionmentioning
confidence: 96%
“…Similar to the findings by Jung Hyun Kwon et al [23] and others [20,24], our study showed a positive association between DHEAS and advanced BA. This relationship is likely due to the higher adrenal androgen levels in children with obesity; these increased levels are believed to be responsible for the advanced BA.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the ndings by Jung Hyun Kwon et al [23] and others [20,24], our study showed a positive association between DHEAS and advanced BA. This relationship is likely due to the higher adrenal androgen levels in children with obesity; these increased levels are believed to be responsible for the advanced BA.…”
Section: Discussionsupporting
confidence: 92%